Enkele treë tot 'n moontlike re-konfigurasie van pastorale terapie? Perspektiewe op ontwikkelende praktyke - J. A. van den Berg; A. de Beer; M. Fourie (Acta Theologica)
In this article perspectives regarding the development and transformation of pastoral care from being only the responsibility of individual ordained professionals towards a model of care for and by the community and its members, are described. In this development the emphasis is placed on pastoral care as a public theological endeavour with a strong strategic component resonating with the character of practical theology. A specific case study derived from the postgraduate program in pastoral therapy in the Department of Practical Theology, Faculty of Theology, University of the Free State, is portrayed. A lecturer and two former students reflect on certain developments in the program using a model of narrative research and reflection. In this description developing and possible alternative perspectives are sketched for possible future developments in the teaching and providing of pastoral therapy.